Anthology of Mark Meerovich’s Рrojects - Grigoryeva, Elena (project baikal, 2019)
Alongside with his teaching and research activity, Mark Meerovich practiced design. At first he designed interiors of flats, houses and small public buildings. Maybe such practice was caused by the necessity to earn extra money: his research activity was not enough to maintain his family. However, Mark brought inspiration into everything he did. It also concerned interiors: they were recognized by the most sophisticated esthetes. This experience was also reflected in his articles – a brilliant series “Philosophy of the Interior” was created together with Konstantin Lidin and published in our journal. The last decade of Mark’s life was filled with large-scale town-planning projects for Irkutsk and Tomsk. This fruitful period started with his participation in the elaboration of the concept for 130 Quarter and then his active monitoring of its realization and further existence. Meerovich cooperated with “Studio 7” and “Siberian Laboratory of Urbanistics” in the Tomsk series (three projects). The collection of his works is culminated with the projects worked out under the auspices of the “Town-Planning School” project organization founded by Mark. These projects include improvement of significant public spaces in Irkutsk and the Irkutsk region.